The Fulfillment of Human Rights in Minahasa Culture and the Reception of Muslim Immigrants in Tomohon: An Analysis from the Perspective of Hospitality - Nelwan, Gerry (Satya Widya: Jurnal Studi Agama, 2025)
Today issues related to human rights continue to be a serious problem, especially in the context of Indonesian society. This problem is often influenced by the attitude of majoritarianism which then has an impact on limiting the rights of others. This research then wants to see how the Minahasa indigenous people accept and provide living space for Muslim immigrants as part of fulfilling human rights. The existence of an attitude of acceptance carried out by the Minahasa indigenous people shows an acknowledgment of identity as fellow citizens. The research process will use a qualitative methodology, data will be obtained through participatory observation, collecting documents, journals, and interviews with informants. The informants were selected based on the intended sample. After collecting data, documents, and interview results, they will then be analyzed with the theory of hospitality from the perspective of Marianne Moyaert. The attitude of hospitality and acceptance from the Minahasa indigenous people can be an opportunity to fulfill everyone's rights based on local culture.